Functional performance evaluation of an alginate/nano-cockle shell powder nanobiocomposite bone scaffold with BMP-2 - Ahmad, Nurnadiah; Bharatham, Hemabarathy; Abd. Hamid, Zariyantey; Perimal, Enoch Kumar; George, Penny (Indian Academy of Sciences, 2019)
Improvement in bone tissue engineered scaffolds plays an important role in determining the healing outcome. This study aims to investigate the functional performance of previously developed nanobiocomposite bone scaffolds using bone morphogenetic protein-2 (BMP-2) for comparative analysis. The structural morphology and porosity of the scaffolds were analysed using scanning electron microscopy prior to dividing them into two groups, BMP-2 treated and control, for the surface mineralization study, in vitro and in vivo evaluation. The surface mineralization study showed the presence of plate-like calcium and phosphorus apatite crystallites in both groups indicative of the mineralization process. Osteoblasts (MC3T3-E1 subclone 4) cultured on the scaffold showed changes in the surface morphology with the presence of mineralization elements and the extensive presence of collagen fibres in BMP-2 scaffolds compared to the control. This was supported by a significant increase in calcium and alkaline phosphatase (ALP) activity showing enhancement in osteoconductiveness. In vivo studies conducted on 20 male ICR albino mice through subcutaneous dorsum implantation of scaffolds for 2 and 4 weeks showed a significant increase in the histological score for inflammatory cells, scaffold degradation and neovascularization at week 4 compared to week 2 for the BMP-2 scaffold. These findings are supported by a significant decrease in ALP activity indicative of scaffold mineralization. There were no significant differences between BMP-2 and control scaffolds within the period of this study. In conclusion, the functional performance of the scaffolds was mildly accelerated in BMP-2 compared to the control scaffold which showed promising properties in supporting osteogenesis without the use of any promoting factors.